1994
DOI: 10.1289/ehp.102-1567252
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between particle size, in vivo particle persistence, and lung injury.

Abstract: Dosimetry parameters such as deposition, clearance, retention, and translocation and dissolution of inhaled particles in and to different lung compartments may be important for the persistence of particles in the lung and may correlate with adverse pulmonary effects. We investigated such correlations using a model involving TiO2 particles of two particle sizes (20 nm diameter, ultrafine; 250 nm diameter, fine) of the same crystalline structure (anatase). A 12-week inhalation experiment in rats resulted in a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
276
1
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(286 citation statements)
references
References 16 publications
6
276
1
3
Order By: Relevance
“…Furthermore, several publications have reported translocation into systemic circulation and accumulation in secondary target organs; these publications have been reviewed recently (Oberdörster et al 2005). This is different from epithelial surface retention observed for micron-sized poly-styrene and glass particles (Lehnert et al 1989; Oberdörster et al 1994). Our data do not provide any information about the interstitial localization of retained NPs.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, several publications have reported translocation into systemic circulation and accumulation in secondary target organs; these publications have been reviewed recently (Oberdörster et al 2005). This is different from epithelial surface retention observed for micron-sized poly-styrene and glass particles (Lehnert et al 1989; Oberdörster et al 1994). Our data do not provide any information about the interstitial localization of retained NPs.…”
Section: Discussioncontrasting
confidence: 82%
“…Furthermore, Ferin and co-workers had shown the uptake of 20-nm ultrafine TiO 2 -particles in epithelial cells and in the interstitial spaces (Ferin et al 1992; Oberdörster et al 1994). Geiser et al (2005) showed that 1 hr after inhalation, 24% of inhaled 22-nm TiO 2 particles were within or beyond the epithelial barrier of the lungs in epithelial and endothelial cells, connective tissue, or capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Oberdörster et al (1994) observed that ultrafine TiO 2 instilled into rats and mice was more proinflammatory than fine TiO 2 , as TiO 2 induced a neutrophilic influx into the lungs. Oberdörster et al (1994) reported that particle surface chemistry is equally or more important in inflammation and acute toxicity.…”
Section: Cons: Pulmonary Morbidity and Mortalitymentioning
confidence: 99%
“…Oberdörster et al (1994) observed that ultrafine TiO 2 instilled into rats and mice was more proinflammatory than fine TiO 2 , as TiO 2 induced a neutrophilic influx into the lungs. Oberdörster et al (1994) reported that particle surface chemistry is equally or more important in inflammation and acute toxicity. Freshly generated polytetrafluethylene (PTFE) fume containing UFPs < 26 nm induced hemorrhagic pulmonary inflammation and death after rats were exposed to 10–30 μg of dust, and aging of UFPs resulted in the loss of surface reactivity and toxicity (Oberdörster et al 1995).…”
Section: Cons: Pulmonary Morbidity and Mortalitymentioning
confidence: 99%
“…Both of these factors may explain some of the location differences in PM 2.5 effects on adverse birth outcomes. Particle size distribution will impact the ability of the particles to become biologically active as it affects lung deposition (Oberdörster et al, 1994; Carvalho et al, 2011). Chemical composition will in part determine the toxicological profile of the particulate matter.…”
Section: Discussionmentioning
confidence: 99%